Research on social governance strategies related to public health risks of sex trading - Guo, Fangxi (Transactions on Social Science, Education and Humanities Research, 2025)
This paper addresses the global public health risks associated with sex work, focusing on both physical and mental health challenges faced by sex workers. The spread of sexually transmitted diseases (STDs), particularly HIV/AIDS, is a major health risk in many regions due to the failure of sex workers and clients to consistently adhere to safety measures such as condom use. Additionally, mental health issues like depression, anxiety, and post-traumatic stress disorder (PTSD) are common among sex workers, exacerbated by social stigma, discrimination, and occupational stress. The paper explores various governance models from countries like Australia, New Zealand, and Sweden, highlighting successful strategies in managing the health risks of sex work. It emphasizes the importance of a comprehensive governance model that combines regulation with support, offering both health and mental health services, legal protections, and social security for sex workers. The paper concludes by recommending policy adjustments and international cooperation to create a more inclusive and supportive environment for sex workers, ultimately improving their health and social outcomes.